Macropsini (Homoptera: Auchenorrhyncha: Cicadellidae: Eurymelinae) from the vicinity of Ambo, Ethiopia - Tishechkin, Dmitri Yu. (Zootaxa, 2019)
Macropsis tincta Tisheсhkin sp. n., M. viridofulgida Tisheсhkin sp. n., M. nikippa Tisheсhkin sp. n., and M. antibia Tisheсhkin sp. n. from the vicinity of Ambo, Ethiopia are described. Redescriptions of M. simplex Jacobi, 1910, M. tuberculata (Linnavuori, 1978), and M. hippodameia Linnavuori, 1978 based on the material from Ambo are given. Apparently, Indian and African Acacia-dwelling Macropsis species represent a separate lineage evolved on Mimosoidea, and dispersed throughout subtropical and tropical regions of the Old World. Acacia-dwelling group of Macropsis demonstrate some morphological trends unknown in Palaearctic species; this makes it necessary to re-evaluate the diagnostic significance of some morphological traits for the taxonomy of Macropsini.